Proceedings of the Proceedings of the 5th Annual International Seminar on Trends in Science and Science Education, AISTSSE 2018 2019
DOI: 10.4108/eai.18-10-2018.2287391
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Virtual Lab Media Using Problem Based Learning Models to Increase Students Learning Achievement Based STIFI and Learning Style Tes

Abstract: This research aims to implement the Virtual Lab media using Problem Based Learning assisted to increasing the students' learning achievements in Cahaya Medan High School and finding out whether there are differences in student learning achievements using virtual lab media and Problem Based Learning models in terms of the STIFIn test and learning style tests This study uses a pretest-posttest group design. Data analysis techniques using One Way Anova analysis. The results showed: (1) there were differences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…Correlating with virtual media, research that has been conducted by Tuysuz (2010), concludes that virtual media can effectively improve student learning outcomes and have a positive impact on character building students (Harefa et al 2020;Silaban, 2021;Panggabean et al 2019). Bilgin research (2009 found that the guided inquiry learning model is a learning model in which the teacher integrates a scientific activity and builds students' thinking patterns simultaneously based on facts, principles and acceptable scientific rules.…”
Section: Resultsmentioning
confidence: 99%
“…Correlating with virtual media, research that has been conducted by Tuysuz (2010), concludes that virtual media can effectively improve student learning outcomes and have a positive impact on character building students (Harefa et al 2020;Silaban, 2021;Panggabean et al 2019). Bilgin research (2009 found that the guided inquiry learning model is a learning model in which the teacher integrates a scientific activity and builds students' thinking patterns simultaneously based on facts, principles and acceptable scientific rules.…”
Section: Resultsmentioning
confidence: 99%
“…Learning in digital integrated laboratories can improve students 'achievement (Panggabean et al 2019;Muchtar et al 2020) and students' metacognitive skills (Pratiwi et al 2019). Meanwhile, learning with guided inquiry integrated practicum can improve science process skills and student learning outcomes (Juniar & Fardilah, 2019).…”
Section: Students' Learning Outcomesmentioning
confidence: 99%
“…Digital accommodating practicum methods such as the use of virtual labs can improve student learning outcomes (Rizky and Simorangkir, 2018;Sugiharti et al 2019) and students' achievements (Panggabean et al 2019). Practicum accommodating digital-based guided inquiry can improve student learning outcomes and scientific processes (Akbar et al 2019;Juniar and Fardilah, 2019), student learning motivation (Harefa, 2018), problem solving skills (Abadi and Bahriah, 2016), students' critical thinking skills (Kurniawati et al 2015;Wardani et al 2017), and practice the science process (Suryaningsih, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The elaboration and development are both in the context of learning media (Muhajarah & Shulton, 2020) and in the context of development as laboratory media (Zhang et al 2016;Luo & Chhabda, 2015;Liem et al 2010). Apart from development, the virtual lab has been widely integrated and collaborated with other online media such as STIFI (Panggabean et al 2019), LabView & myDAQ (Prakash et al 2017), SVM classification (Hristova et al 2021), and based on VirtualBox (Anam et al 2020) and through integration with science e-learning (Liu et al 2015) in an effort to optimize its implementation.…”
Section: Introductionmentioning
confidence: 99%